2012
DOI: 10.1007/s13593-011-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher sustainability performance of intensive grazing versus zero-grazing dairy systems

Abstract: Although grazing of dairy cows is an integral part of dairy farming in many European countries, farmers today more often choose for zero-grazing systems, where cows are housed throughout the year. Some studies already compared grazing and zero-grazing systems for specific issues such as labor efficiency, environmental impact, or animal welfare. In our study, we perform a more integrated evaluation, considering relevant ecological, economic, and social aspects. This allows for a balanced and more complete compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 28 publications
(47 reference statements)
5
42
0
11
Order By: Relevance
“…In our study, irrigation represented 87.9% of the total amount of water applied to maize, implying that such it exerts the highest pressure on groundwater of the forage crops existing in the area. These results agree with previous assessments in temperate countries showing that the development of forage systems based on maize may exacerbate pressure on groundwater (Meul et al, 2012). DM yields for all fodder crops were highly variable among farms and appear to be lower than those in recent references, for example in the case of berseem clover (Vasilakoglou and Dhima, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, irrigation represented 87.9% of the total amount of water applied to maize, implying that such it exerts the highest pressure on groundwater of the forage crops existing in the area. These results agree with previous assessments in temperate countries showing that the development of forage systems based on maize may exacerbate pressure on groundwater (Meul et al, 2012). DM yields for all fodder crops were highly variable among farms and appear to be lower than those in recent references, for example in the case of berseem clover (Vasilakoglou and Dhima, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the environmental and economic sustainability, our results show that increasing the EA level allows the farms to have better environmental and economic results. From an environmental point of view, several studies have reported that farms using fewer concentrates and mineral fertilisers have lower nitrogen surplus and energy consumption (Hansen et al, 2001;Paccard et al, 2003;Meul et al, 2012). In our case study, this relationship was established whatever the unit in which the indicators were expressed: per hectare or per unit of product.…”
Section: Discussion and Perspectivesmentioning
confidence: 54%
“…Including higher proportions of forage in the diet constitutes a possible path to reduce the use of concentrates without decreasing the output level. It could be achieved through the optimisation of forage and grassland management, and by avoiding losses during grazing, harvesting, preservation and feeding (Meul et al, 2012). Havet et al (2014) mentioned as an example the use of grassland calendars with a visual assessment of the grass height to optimise the management of grass quality during rotational grazing.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…During tool development, the aims of the tool developers are not always clear or cannot always be fulfilled (Triste et al 2014). Additionally, the tool used in practice can offer different functions, irrespective of the developers' aim during development (Langeveld et al 2007, Schader et al 2014): a tool can provide a platform for communication through describing the sustainability themes, i.e., communication function (De Mey et al 2011); it can promote the exchange of ideas and knowledge, i.e., learning function (Terrier et al 2010, De Mey et al 2011, Gerrard et al 2011, and further induce management responses, i.e., management function (Grenz et al 2009); and it can fulfill monitoring obligations (Wiek and Binder 2005, Grenz et al 2009, Meul et al 2012) for statutory control purposes or for product certification, i.e., monitoring and certification function (Hülsbergen 2003, Rodrigues et al 2010. Furthermore, the methodological steps within tools may contain significant biases toward specific framings of sustainability (Bond and Morrison-Saunders 2011).…”
Section: Variation In Sustainability Assessment Toolsmentioning
confidence: 99%